2001
DOI: 10.1038/sj.jhh.1001193
|View full text |Cite
|
Sign up to set email alerts
|

Urinary albumin excretion in lean, overweight and obese glucose tolerant individuals: its relationship with dyslipidaemia, hyperinsulinaemia and blood pressure

Abstract: The presence of microalbuminuria has become an important tool for therapeutic intervention. In this study we investigated whether the dysmetabolic syndrome of obesity was associated with or could occur in the absence of microalbuminuria. The study was conducted in 71 clinically healthy, glucose tolerant Hispanics (age: 43 ؎ 1.4 years, body mass index (BMI): 28.7 ؎ 0.6 kg/m 2 , systolic blood pressure (SBP): 117 ؎ 2 mm Hg, diastolic blood pressure (DBP): 77 ؎ 1.3 mm Hg, urinary albumin excretion: 10.2 ؎ 0.6 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
5
20
1
1
Order By: Relevance
“…There was an increase in mean urine albumin excretion as the BMI increases [ Fig.4] in tertiles, but it did not reach statistical significance. Similar observations were made by Cubeddu and Hoffmann [41].They reported that there is no significant relationship between obesity and micro albuminuria and found no difference in albumin excretion in obese glucose tolerant subjects with high BMI.Yesim et al [42] also reported the same in their study on obese and lean women without T2DM.…”
Section: Discussionsupporting
confidence: 74%
“…There was an increase in mean urine albumin excretion as the BMI increases [ Fig.4] in tertiles, but it did not reach statistical significance. Similar observations were made by Cubeddu and Hoffmann [41].They reported that there is no significant relationship between obesity and micro albuminuria and found no difference in albumin excretion in obese glucose tolerant subjects with high BMI.Yesim et al [42] also reported the same in their study on obese and lean women without T2DM.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, contradictory results derived from apparently healthy, glucose-tolerant subjects suggest that MA is not necessarily related to IR. [12][13][14][15] In the present study, apparently healthy subjects were carefully selected based on a fasting plasma glucose o100 mg/dl and having a normal blood pressure. The data supports a lack of relationship between MA and IR as assessed from the HOMA model.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Studies of glucose-tolerant subjects suggested that IR is not always associated with MA. [12][13][14] Some studies suggested that abdominal obesity is independently associated with MA, [15][16][17][18][19][20] whereas others showed that abdominal obesity is not related to the albuminuria level. 12,13 The latter studies may have been biased by factors such as a small sample size and the former studies did not exclude subjects with high-normal blood pressure or hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] However, recent studies conducted in type 2 diabetic patients revealed that even very low UAE rates, below those conventionally accepted as the lower limit to define microalbuminuria (o30 mg per 24 h), were also associated with increased mortality. 15 Similarly, in non-diabetic subjects, albuminuria of o30 mg day À1 was found associated with older age, male gender, smoking, obesity, elevated blood pressure, left ventricular hypertrophy, dyslipidaemia, hyperinsulinaemia, salt sensitivity, lack of nocturnal BP dipping [15][16][17][18][19] and increased risk of coronary heart disease and death 10,15,[20][21][22][23][24][25] (Table 1). In non-diabetic hypertensive individuals with left ventricular hypertrophy, the risk for cardiovascular morbidity and mortality increased continuously as the UAE increased.…”
mentioning
confidence: 96%